Análise de sensibilidade da migração ao modelo de velocidades - SILVA, Francisco Josa Coutinho (2019)
Migration algorithms are based on ray theory aproximations or wave equation. Whatever the case, the migration velocity model must be kinematically equivalent to the velocity distribution in the subsurface. The estimation of such a velocity model in depth requires robust algorithm, mainly when the medium presents strong lateral velocity variations. In this case, the migration algorithms themselves can be used to validate the velocity model. This work explores this approach using two migration algorithms. The Kirchhoff migration and downward continuation migration. The theory of common image gathers is discussed and applyed to the Marmousi synthetic data set.